Avaliação qualitativa das águas no sistema de macrodrenagem da bacia do Tabuleiro dos Martins – Maceió/AL - Sá Filho, José Adriano Rocha de (2010)
The purpose of this research is to show the problems of infrastructure in the city of Maceió, resulting in frequent flooding, mainly in the lower area of the basin of the Tabuleiro do Martins, causing negative impacts, particularly those that comes from by the pollutant load carried by the runoff. As a result, this region was put into practice the Macrodrenagem project, compounding three detention lagoons, including the lagoons 1 and 2 were connected by watercourses with the lagoon 3, and that with the river Jacarecica. Order to know the limnological characteristics of the system that makes up the Macrodrenagem of the basin of Tabuleiro do Martins, for further assessment of negative impacts, a basic diagnosis was made by the physical–chemical aspects: water temperature and air, true color, turbidity, total dissolved solids, total suspended solids, fixed and volatile, pH, conductivity, dissolved oxygen, DBO5, DQO, ammonia nitrogen, nitrite, total phosphorus and chloride, and biological: total coliforms and thermotolerants. For this, samples were collected from June to November 2007 in seven sampling points, which three were located in the lagoon 1; one on the lagoons 2 and 3, another in the course of water formed by the excess water accumulated in these lagoons, in addition to the discharge of “Coca-cola” in the lagoon 1. In addiction to was made a general characterization of the basin, emphasizing the climate and the aspects climates and the use and land use. These variables were statistically analyzed and correlated with the limits established by CONAMA 274/2000 and 357/2005, and the Decree 6200/1985. The studies made have shown that rainwater also served for disposal of sewage, indicating that the detention lagoons were environmentally threatened with many of its limnological parameters out of the standards established by the analyzed legislation. The multiple uses of water bodies studied were inviable by the high levels of thermotolerants coliforms, DBO5 and total phosphorus, and low of dissolved oxygen, while the discharge of the soft drinks manufactures “Coca-cola” showed all the concentrations of DQO higher than the maximum value established for issue of industrial wastewater in Alagoas State.